Análise de viabilidade sustentável de micro-empresa de serviços de arquitetura por meio do pensamento sistêmico - Dietrich, Renata Kohmann (Universidade do Vale do Rio dos Sinos, 2013)
Nowadays organizations are working in an increasingly dynamic and interrelated environment context, where multiple forces act and influence their results, not being possible anymore the fragmented look of the parts to solve the more and more complex problems these organizations must face. This work has the purpose to use Systems Thinking as a tool to analyze and comprehend the actual context of a small architecture business, providing knowledge and skills to this organization to produce strategic changes to achieve its goals through a sustainable growth.
Keywords: Pensamento sistêmico; Organizações que aprendem; Arquitetura; Systems thinking; Learning organizations; Architecture